محمد عبد الرضا جاسم الدوخي تاثير النحاس على اسجة غلاصم يافعات اسماك البني - محمد عبد الرضا (مجلة علوم ذي قار, 2019)
Gill structure of Barbus sharpeyi (Gunther) juveniles has been studied, they were exposed to various concentrations of copper. Gill damage resulting from exposure to sub lethal concentrations. Histological changes in the gills included hyperplasia of the gill tissue, some engorgement with bleeding in the secondary lamellae, epithelial separation, necrosis, and fusion of adjacent secondary lamellae. The result of experiment shows that the behavior of susceptible fishes to high concentration(3ppm) after 3 hr. of exposure to the ion, starting with swimming close to water surface circulation movement and hemorrhage in gill lamella.